Investigating cADPR and NAADP in intact and broken cell preparations. - Morgan, A; Galione, A (2008)
The body of literature characterizing cyclic adenosine diphosphoribose (cADPR) and nicotinic acid adenine dinucleotide phosphate (NAADP) as Ca2+-mobilizing second messengers is growing apace. However, their unique properties may, for the uninitiated, make them difficult to work with. This article reviews many of the available techniques (and associated pitfalls) for investigating these nucleotide messengers, predominantly focusing upon optical techniques using fluorescent reporters to measure Ca2+ in the cytosol as well as Ca2+ or pH within the lumen of intracellular organelles.